Dilemma of nominee directors: Finding the best practice - Hassan, Halyani (ICSSAM International Conference on Social Science and Management - ISEPSS International Symposium on Education, Psychology and Social Sciences, 2014)
Directors as the manager and decision maker in a company are subjected to certain duties provided by the legislated act as well as the Common law. In certain companies, such as state owned companies, subsidiary companies or where the shareholders consists of institutional investors the board of directors of those companies may consists amongst them nominee director/s. Nominee directors are appointed as representatives of their nominators. They are expected to safeguard the rights of their nominators. Generally, the provisions in the statutes governing company matters which emphasize on directors‘ duties do not differentiate the duties imposed on any of the directors regardless of whatever type of director that they belong to. Thus they would found themselves in a dilemma as they owe their loyalty to both the company as well as to their nominators. This paper seeks to explore the legislation and the case laws in other countries (Singapore, Australia and United Kingdom) besides Malaysia, as regards to the duty of nominee directors. It would be beneficial to study whether these countries had provided any specific provisions to the nominee directors in order to guide them in discharging their duties or to neutralize their dilemma. The paper would conclude by suggesting the best practice for the nominee directors in performing their duties and to strike a balance between their duties to the company and to their nominators.